Consumer Perception of Selecting Brand: A Comparative Study between Pepsi Cola and Mojo Cola - Hossain, Md. Kamal; Kumar, Subrata; Rahman, Mohammad Ataur (Global Disclosure of Economics and Business, 2016)
Consumers are so much conscious and sensitive in case of selecting brand .This study investigates the impact of consumer’s perception in selecting beverage products between Pepsi cola & Mojo cola. A survey was conducted by a significant number of respondents from the Pabna University of Science & Technology & surrounding areas. The data analyses were conducted by descriptive factor analysis, statistical tools & technique. The results revealed that the most of the consumers are highly concerned about the perception of brand regarding selection of Pepsi cola & Mojo cola beverage drinks. This is a relatively new issue that remains largely undiscovered by researchers under our country’s perspective. It is hoped that the findings may assist the local (Akij Beverage Ltd.) and multinational (Transcom Beverage Ltd.) beverage companies about the necessities of enhancing their brand perception. The paper adds to the existing body of research on beverage consumers particularly on consumer’s perceptions and expectations from these brands.